A Various Forms Of Expression Of Mortal Experience Among Urban Sufism (Study On The Qadiriyyah Wa Naqsyabandiyyah Tariqah Group In Lampung) - Pratama, M. Guntur Sandi; Ramadhan, M Syafrie (Jurnal Spiritual Healing, 2023)
This paper aims to determine the various forms of expression of mortal experience among urban Sufism: a study on the Qadiriyyah wa Naqsyabandiyyah tariqah group in Lampung. This paper is a type of field research, data collection methods: observation, interviews and documentation, which the author conducted at the Thalabul Ilmi Al-Hanif Lampung Council, located in Teluk Betung Barat, Bandar Lampung City. The method of analysis uses a phenomenological approach. The results of this study show that there are several kinds of related mortal experiences in the MTI Al-Hanif Lampung assembly, experienced by pilgrims based on surah Al-Anfal verse 2, so they use these propositions to understand the experiences that occur to them. Some of these Sufis wept, screamed and were silent in various forms of mortal expression carried out by them.